KNOWLEDGE OF POTENTIAL/ACCESSIBILITY OF FINANCIAL CREDITS IN RURAL AREAS IN OLT COUNTY - Corina CRUCERU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
The orientation of research activity of present situation regarding the current level of financial credit in rural areasof the Olt county required to carry out investigations on both the borrowers (farms) and the lenders (banks,financial institutions) in the county. As working methods were used questionnaires, questions being designedspecifically for borrowers and lenders. The questionnaire contained 32 questions. There have been investigatedhouseholds from Slatina and Caracal rural areas in Olt county. All elements presented for rural areas in the Oltcounty revealed the local,s attitude and behavior In taking loans, with insignificant differences between Slatina andCaracal rural areas.